Association between maternal lipid levels during pregnancy and delivery of small for gestational age: A systematic review and meta-analysis - Wang, Yuan; Chen, Zhifang; Zhang, Feng (Frontiers in Pediatrics, 2022)
BACKGROUND: Studies investigating the relationship between gestational dyslipidemia and small for gestational age (SGA) have reported differing results. This review was performed to determine whether maternal lipid levels during pregnancy were associated with SGA. METHODS: Literature searches for relevant studies were conducted systematically from establishment until February 2022 with PubMed, Embase, Cochrane Library and Web of Science. Risk of bias was assessed with the Newcastle-Ottawa Scale and 11-item checklist. According to the classification of GHD parameters, meta-analyses reporting cases regarding total cholesterol (TC), triglycerides (TG), low-density lipoprotein-cholesterol (LDL-C) and high-density lipoprotein-cholesterol (HDL-C) were performed respectively. If I2 ≥50%, considered to demonstrate substantial heterogeneity, the random effect model was employed. Otherwise, a fixed effect model was employed. RESULTS: Eight studies (14213 pregnancies) were included. Decreased levels of TC (MD -0.13; 95% CI -0.24 to -0.02), TG (MD -0.09; 95% CI -0.14 to -0.03) and LDL-C (MD -0.12; 95% CI -0.23 to -0.00) were risk factors for SGA infant birth. No evident association was observed between HDL-C and delivery of SGA (MD -0.08; 95% CI -0.19 to 0.02). CONCLUSIONS: Gestations complicated with dyslipidemia, especially lower concentrations of TC, TG and LDL-C, were at significantly higher risk of delivery of SGA.